The Effect of Fisheries Productivity, Socioeconomic Factor, Non-Fisheries Business Opportunity on Vulnerability and Poverty: Small-Scale Fisheries in Riau Islands, Indonesia - Zulkipli Zulkipli; Ujianto Ujianto; Tri Andjarwati (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: to prove and analyze the effect of fisheries productivity, social-economic factors, and non-fisheries business opportunity on vulnerability and poverty of small-scale fisheries in Lingga Regency, Riau Islands, Indonesia.